Tax Me If You Can! Optimal Nonlinear Income Tax between Competing Governments - Etienne Lehmann; Laurent Simula; Alain Trannoy (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate how the optimal nonlinear income tax schedule is modified when taxpayers can evade taxation by emigrating. We consider two symmetric countries with Maximin governments. Workers choose their labor supply along the intensive margin. The skill distribution is continuous, and, for each skill level, the distribution of migration cost is also continuous. We show that optimal marginal tax rates are nonnegative at the symmetric Nash equilibrium when the semi-elasticity of migration is decreasing in the skill level. When the semi-elasticity of migration is increasing in the skill level, either optimal marginal tax rates are positive everywhere or they are positive for the lower part of the skill distribution and then negative. Numerical simulations are calibrated using plausible values of the semi-elasticity of migration for top income earners. We show that the shape of optimal tax schedule varies significantly, depending on the profile of the semi-elasticity of migration over the entire skill distribution - a profile over which we lack empirical evidence.
Keywords: D82; H21; H87; 330; optimal income tax; income tax competition; migration; labor mobility; Nash-equilibrium tax schedules